A Management Model for Galleries, Libraries, Archives, and Museums (GLAM) at Hatta Heritage: Strategies for Internalization and Dissemination - Majidah, Majidah; Hasfera, Dian; Fadli, Muhammad (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2025)
This research aims to develop an integrated management model designed explicitly for the Galleries, Libraries, Archives, and Museums (GLAM) sector to enhance the dissemination of information related to Proclamatory Bung Hatta. This study adopts a qualitative approach. Data were collected through interviews, observations, and literature reviews to understand the research topic comprehensively. Key informants included librarians, museum managers, curators, and information users, whose perspectives provided valuable insights into the dynamics of information utilization. The research was conducted in Bukittinggi City, considering Bung Hatta’s hometown, as there are several GLAM institutions related to Bung Hatta in Bukittinggi City. The findings were then synthesized into a conceptual model. The findings of this study led to the development of an information packaging model tailored to the needs of the Bung Hatta collection. The model consists of several key stages: identifying relevant content, choosing the most suitable formats, reprocessing the information to suit user needs, organizing it in a coherent structure, and finally, disseminating it effectively. Each stage is designed to ensure that the values and messages embedded in the collection can be more easily understood, appreciated, and accessed by a wider audience.